Longitudinal Relationships Between Reading Abilities, Phonological Awareness, Language Abilities and Executive Functions: Comparison of Low Risk Preterm and Full-Term Children - Pérez-Pereira, Miguel; Martínez-López, Zeltia; Maneiro, Lorena (Frontiers in Psychology, 2020)
Different investigations have found that very or extremely (high risk) preterm children show global or specific difficulties in phonological awareness (PA) and reading abilities. Do low risk preterm children, however, exhibit this pattern? Phonological awareness has been considered an important predictor of literacy. Certain executive functions (EFs), and language abilities in turn, have been found to predict PA. The aims of this study are (1) to compare reading abilities of low risk preterm children of different gestational age (GA) groups to those of full-term children, (2) to compare the performance of low risk preterm children of different GA groups to that of full-term children in different EFs, language measures and PA, and (3) to perform a path analysis in order to test a longitudinal model of the relationships between EFs, language abilities, PA and reading. The participants were 108 low risk 4- year-old preterm children, classified into 3 groups of different GAs, and 34 full-term children. The children’s EFs (rapid automatized naming task (RAN), working memory, and inhibition) were assessed at 4 and 5 years of age. Vocabulary comprehension, morphosyntactic production and grammar reception were assessed when the children were 5 years of age, as well as phonemic awareness and syllabic awareness. Finally, reading abilities were assessed when the children were 9 years old. No significant difference between gestational age groups was found on any of the measures taken on EFs, language abilities, phonological awareness, or reading abilities. The path analysis model demonstrates the direct effect of working memory, certain linguistic skills governed by rules (grammar, morphology) and phonological awareness on reading abilities at 9 years of age. The model also shows the mediating role that PA has on the relationship between EFs and language abilities with reading abilities.